Evaluation of immunophenotypic expressions of plasma cells in plasma cell myeloma patients and its association with prognostic factors and clinical stages - Chi, Ling Pei (2021)
Introduction: Neoplastic plasma cell expresses aberrant markers which differ from normal plasma cell was postulated to carry prognostic significance. This study aimed to determine the proportion of immunophenotypic expression of plasma cells in plasma cell myeloma patients at diagnosis and to study the association between these markers with clinical and laboratory parameters. Methods: A retrospective study was carried out from June 2016 till June 2019 by collecting the flow cytometry results (CD38/CD138/CD19/CD45/CD56/CD117 and cytoplasmic kappa and light chains expression) from newly diagnosed plasma cell myeloma, PCM cases in both Hospital Kuala Lumpur and Hospital USM. Clinical data and laboratory results retrieved from medical record were analyzed statistically using SPSS26.0. Results: All 78 cases of flow cytometry results in newly diagnosed PCM had more than one aberrant antigen expression with 100% expression rate for both CD38 and CD138 while CD19/CD45/CD56/CD117 in 28.2%, 23.1%, 83.3% and 25.6% respectively. The majority were expressed kappa light chain restriction, 60.3%. A significant association was demonstrated between CD19 markers with serum creatinine (p=0.036). However, there was no significant association between expression of other immunophenotypic markers with its associated factors. Conclusion: Immunophenotyping by multiparametric flow cytometryisausefultoolfordistinguishingneoplasticplasmacellsfromnormalplasma cell where aberrant antigens were present in most of thePCM withaheterogenous immunophenotypic profile of PCM were defined in our population as compared to others. Moreover, there was a significant association demonstrated between CD19 with serum creatinine. However, this result should be confirmed with a bigger sample size.